El afecto y su incidencia en el desarrollo integral de los estudiantes de tercer año de educación básica de la unidad educativa 5 de Junio, Parroquia Isla de Bejucal, cantón Baba, Provincia los Ríos. - Garcés Bustamante, Jennifer (2016)
In this research work we began with the problematic situation that affects the students of the Educational Unit of the Isla de Bejucal Parish as is literacy and its influence on reading comprehension Preceded by the stated objectives that indicate the correct way Where our research is going. In addition, this research work is based on its theoretical framework. This paper also presents a proposal which is our alternative solution to the problem raised Our research work is made up as follows: In the first chapter, it deals with the subject or idea of the research, followed by the contextual framework with its different contexts in which our research is immersed, then the problematic situation presented by the educational unit, the approach of the problem, the delimitation of the Research, then the reason why we perform this work justification and objectives both the general and the specific. In the second chapter, we find the theoretical or referential framework that is conformed by the conceptual framework, the frame of reference within this we have to the research background and the category of analysis, we find also the theoretical posture, the hypotheses both general and sub Hypotheses and their variables. The third chapter demonstrates the results of the research in which we find the analysis and interpretation of data obtained in the application of the survey, conclusions and recommendations both specific and general.